Involving certain socio-demographic groups of the population in active entrepreneurship as a factor of sustainable regional economies - T. A. Ilyushnikova (Вестник университета, 2024)
The article examines priority groups of   the population (socially vulnerable, women entrepreneurs, young and social entrepreneurs) engaged in entrepreneurial activities, including through the conclusion of a  social contract, as a   factor of   the sustainability of   regional economies. The article is   aimed at  analysing the regional structure of   these population groups and their support in  individual subjects. The methodology of   the study is   based on   the use of   general scientific methods (analysis, synthesis, comparison). The main results of   the work have showed that supporting participation of   the above-mentioned groups socially integrates them, stimulating economic growth, regional and national development. In  addition, it  increases the level of   economic competitiveness, expands entrepreneurial opportunities, and creates a  favourable climate for the successful functioning of   market entities. The scope of   application of   the results obtained during the study is   based on   the possibility of   using them while developing mechanisms for increasing the involvement of   the considered priority population groups in   order to  achieve a   given level of   sustainability of   regional economies, which also determines the prospects for further research on  this problem. The dependence of   the level of   sustainable development of   regional economies and their competitiveness on   the level of   involvement of   these groups in   entrepreneurship has been established.